Elucidation of the Bulging Effect by an Improved Ray‐Tracing Algorithm in Deep Penetration Wire Feed Laser Beam Welding and Its Influence on the Mixing Behavior. Issue 6 (29th January 2022) - Bachmann, Marcel; Meng, Xiangmeng; Artinov, Antoni; Rethmeier, Michael
Abstract : Herein, an improved ray‐tracing routine using a virtual mesh refinement approach is adopted in a 3D transient multiphysics computational fluid dynamics model for deep penetration wire feed laser beam welding. In a previous study, it was shown that the improved localization of the reflection points of the subrays within the keyhole leads to a more realistic development of the keyhole depth being validated with experimental results. Another effect investigated in detail herein is a drastic change in the flow behavior in the weld pool, which promotes the occurrence of a necking area in the solidification line and subsequent bulging under specific circumstances. This has a detrimental effect on the filler material element transport in the weld pool, leading to an inhomogeneous dilution of the added material. The numerical observations are backed up by experimentally obtained data, allowing to provide a clear physics‐based explanation of the reduced mixing behavior of the filler wire in the melt pool. Abstract : Herein, experimental and simulation results of laser beam welding with filler wire are presented. Numerical improvements of the utilized ray‐tracing approach for energy–matter coupling thus clarifying the occurrence of bulging and necking effects of the weld geometry and its influence on the mixing of the filler wire in the melt are shown.